The 5-HT4 receptor: molecular cloning and pharmacological characterization of two splice variants. - Gerald, C (1995)
Molecular cloning efforts have provided primary amino acid sequence and signal transduction data for a large collection of serotonin receptor subtypes. These include five 5-HT1-like receptors, three 5-HT2 receptors, one 5-HT3 receptor, two 5-HT5 receptors, one 5-HT6 receptor and one 5-HT7 receptor. Molecular biological information on the 5-HT4 receptor is notably absent from this list. We now report the cloning of the pharmacologically defined 5-HT4 receptor. Using degenerate oligonucleotide primers, we identified a rat brain PCR fragment which encoded a '5-HT receptor-like' amino acid sequence. The corresponding full length cDNA was isolated from a rat brain cDNA library. Transiently expressed in COS-7 cells, this receptor stimulates adenylyl cyclase activity and is sensitive to the benzamide derivative cisapride. The response is also blocked by ICS-205930. Interestingly, we isolated two splice variants of the receptor, 5-HT4L and 5-HT4S, differing in the length and sequence of their C-termini. In rat brain, the 5-HT4S transcripts are restricted to the striatum, but the 5-HT4L transcripts are expressed throughout the brain, except in the cerebellum where it was barely detectable. In peripheral tissues, differential expression was also observed in the atrium of the heart where only the 5-HT4S isoform was detectable.